Cobalt phosphide nanowires as efficient near-infrared light-driven antibacterial agents with high stability and cytocompatibility. (17th September 2021) - Yin, Yixin; Ma, Linmao; Yan, Yuanyuan; Han, Hecheng; Zheng, Luning; Li, Xiaoyan; Xu, Xin
Abstract: Rapid emergence of antibiotic-resistant bacteria has brought huge threat to global healthcare systems. Alternative strategies are urgently needed to fight against these superbugs. In this study, we synthesized a series of cobalt phosphide nanoarchitectures and characterized their physicochemical properties as well as their antibacterial activities. We found that all nanomaterials showed an impressive photothermal property as indicated by their strong near-infrared (NIR) absorption capacity. In particular, 1D-CoP nanowires exhibited the optimal photothermal efficiency due to their higher aspect ratio. Under NIR light illumination, the temperature of the 1D-CoP nanowires suspension was increased by 45.4 °C within 20 min. In contrast, the temperatures of 2D-CoP nanoplates and 3D-CoP nanocubes were increased by 25.5 °C and 26.9 °C, respectively. The growth of planktonic bacteria can be effectively inhibited by 99% within 30 min under NIR irradiation with the presence of 1D-CoP nanowires in suspension. In comparison, up to 60% of the bacteria could be killed when treated with 2D-CoP nanoplates and 3D-CoP nanocubes. Moreover, all nanomaterials displayed high cytocompatibility. This work emphasizes that the anisotropy plays an important role in governing the photothermal properties of NIR-driven materials. Furthermore, the application of CoP nanowires is a promising strategy to treat antibiotic-resistant bacteria.